Pengaruh Penerapan Collaboration Tools: Office365 Terhadap Produktivitas Kerja Pegawai KPKNL Jember - Sari, Titis Ratna; Syahrinullah, Syahrinullah (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2022)
The change in the new way of working in all sectors of work, becomes a very crucial thing. The government sector was not spared from the flow of increasingly modern and rapid changes. This change certainly has a significant impact, not only for business processes, but also the adaptation of human resources in dealing with it. The flexibility of working space implemented by the Ministry of Finance is one of the answers in facing the challenges of new ways of working. Do not stop at the flexibility of the working space alone, now the Ministry of Finance increases the ease of working anywhere through collaboration tools: Office 365. KPKNL Jember as one of the vertical units of the Ministry of Finance participated in the use of this collaboration tool. The purpose of using this tool is to increase work productivity for employees to work flexibly in terms of location and time and not make dependence on the presence of documents or physical storage media. The research method used using qualitative research methods through interviews, observations and documentation the results showed that there is a significant influence in the application of collaboration tools: Office 365 on employee productivity KPKNL Jember, especially for employees who move to official Affairs, these tools make it easy to do hybrid work that is not fixated on face-to-face work relationships and support the balance of employee roles in work and personal life.